1994
DOI: 10.1183/09031936.94.07122146
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms related to asthma and chronic bronchitis in three areas of Sweden

Abstract: S Sy ym mp pt to om ms s r re el la at te ed d t to o a as st th hm ma a a an nd d c ch hr ro on ni ic c b br ro on nc ch hi it ti is s i in n tWheezing was reported by 20.5%, and the combination of wheezing without a cold and wheezing with breathlessness by 7.4%. The use of asthma medication was reported by 5.3%. Long-term cough and/or morning cough together with problems with phlegm was reported by 12.8%; the prevalence being highest in the most polluted area (Göteborg). When using multivariate analysis, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
3
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 25 publications
(43 reference statements)
6
72
3
1
Order By: Relevance
“…On the other hand, the use of snuff is more common among young men. 18 Although smoking has decreased since 1990 when the overall smoking prevalence among adults aged 20-44 years in Sweden was 30-40%, 20 we were surprised by the high smoking prevalence we found among young women. The present smoking prevalence is, in fact, comparable to that found in a study in Northern Sweden in 1996.…”
Section: Table 2 Association Between Different Independent Variablesmentioning
confidence: 45%
See 2 more Smart Citations
“…On the other hand, the use of snuff is more common among young men. 18 Although smoking has decreased since 1990 when the overall smoking prevalence among adults aged 20-44 years in Sweden was 30-40%, 20 we were surprised by the high smoking prevalence we found among young women. The present smoking prevalence is, in fact, comparable to that found in a study in Northern Sweden in 1996.…”
Section: Table 2 Association Between Different Independent Variablesmentioning
confidence: 45%
“…25 The Swedish part of the European Community Respiratory Health Survey (ECRHS) with an age distribution from 20 up to 44 years did not report prevalence by age group, but the overall prevalence of bronchitis symptoms was similar to ours, although our study sample was considerably younger. 20 As symptoms of bronchitis tend to increase with age, 12,24 a comparison with the ECRHS results also suggests an increase in young subjects.…”
Section: Table 2 Association Between Different Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 40% of the incident cases of asthma reported hay fever. In studies based on prevalent cases, the proportion of asthmatics with rhinitis or hay fever is even greater [2,29].…”
Section: Discussionmentioning
confidence: 99%
“…(7) Studies have discovered a female predisposition to cough and have shown that angiotensin-converting enzyme inhibitors induce cough more often among women than among men. (8)(9)(10) The greater female predisposition to cough has been attributed to increased cough reflex sensitivity. (11,12) Awareness of demographic and environmental factors associated with the development of cough could promote early identification, increase prevention of such factors and improve treatment of respiratory conditions.…”
Section: Introductionmentioning
confidence: 99%